2023
DOI: 10.3389/fpsyt.2023.1089724
|View full text |Cite
|
Sign up to set email alerts
|

Higher stress response and altered quality of life in schizophrenia patients with low membrane levels of docosahexaenoic acid

Abstract: Schizophrenia is a severe, chronic, and heterogeneous mental disorder that affects approximately 1% of the world population. Ongoing research aims at clustering schizophrenia heterogeneity into various “biotypes” to identify subgroups of individuals displaying homogeneous symptoms, etiopathogenesis, prognosis, and treatment response. The present study is in line with this approach and focuses on a biotype partly characterized by a specific membrane lipid composition. We have examined clinical and biological da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…More recently, a study on stabilised schizophrenia patients found two subgroups of patients: the DHA group (N = 19) with a lower proportion of membrane DHA as compared to the general population, and the DHA n group (N = 18) with a normal proportion of DHA. DHA patients had more hospitalisations and a lower quality of life than DHA n patients [68].…”
Section: Membrane Lipids For Personalised Medicinementioning
confidence: 87%
“…More recently, a study on stabilised schizophrenia patients found two subgroups of patients: the DHA group (N = 19) with a lower proportion of membrane DHA as compared to the general population, and the DHA n group (N = 18) with a normal proportion of DHA. DHA patients had more hospitalisations and a lower quality of life than DHA n patients [68].…”
Section: Membrane Lipids For Personalised Medicinementioning
confidence: 87%